Optimasi Kinerja Sistem Komputer: Pendekatan Ilmiah untuk Meningkatkan Produktivitas Teknologi - Abdul Sakti (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2024)
This research investigates the effectiveness of new methods in improving computer system performance through a rigorous scientific approach. The research method applied includes the steps of data collection, implementation of new methods, data analysis, and evaluation of results. The research results show that the proposed innovative approach successfully improves the performance of the computer system in various test scenarios. Key findings include significant improvements in data processing speed, with increased system responsiveness and more optimal resource use efficiency. Statistical analysis shows a 25% increase in data processing speed and up to 20% improved resource usage. These results provide a strong empirical basis for the recognition of a scientific approach in improving computer system performance, as well as demonstrating the potential for further application in the context of computer system performance optimization. Thus, this research provides a valuable contribution to the understanding and practice of computer system performance optimization.